CASK and CaMKII function in the mushroom body α′/β′ neurons during Drosophila memory formation - Malik, Bilal R.; Gillespie, John M.; Hodge, James J. (Frontiers in Neural Circuits, 2013)
CaMKII is a central molecule in mechanisms of synaptic plasticity and memory. A vital feature of CaMKII in plasticity is its ability to switch to a calcium (Ca2+) independent constitutively active state after autophosphorylation at threonine 287 (T287). A second pair of sites, T306 T307 in the calmodulin (CaM) binding region once autophosphorylated, prevent subsequent CaM binding and inactivates the kinase during synaptic plasticity and memory. Recently a synaptic molecule called CASK has been shown to control both sets of CaMKII autophosphorylation events and hence is well poised to be a key regulator of memory. We show deletion of full length CASK or just its CaMK-like and L27 domains disrupts middle-term memory (MTM) and long-term memory (LTM), with CASK function in the α’/ß’ subset of mushroom body neurons being required for memory. Likewise directly changing the levels of CaMKII autophosphorylation in these neurons removed MTM and LTM. The requirement of CASK and CaMKII autophosphorylation was not developmental as their manipulation just in the adult α’/ß’ neurons was sufficient to remove memory. Overexpression of CASK or CaMKII in the α’/ß’ neurons also occluded MTM and LTM. Overexpression of either Drosophila or human CASK in the α’/ß’ neurons of the CASK mutant completely rescued memory, confirming that CASK signalling in α’/β’ neurons is necessary and sufficient for Drosophila memory formation and that the neuronal function of CASK is conserved between Drosophila and human. At the cellular level CaMKII overexpression in the α’/ß’ neurons increased activity dependent Ca2+ responses while reduction of CaMKII decreased it. Likewise reducing CASK or directly expressing a phosphomimetic CaMKII T287D transgene in the α’/ß’ similarly decreased Ca2+ signalling. Our results are consistent with CASK regulating CaMKII autophosphorylation in a pathway required for memory formation that involves activity dependent changes in Ca2+ signalling in the α’/ß’ neurons.